PENGARUH VARIASI TINGGI SUDU TURBIN DARI TINGGI BASIN TERHADAP DAYA DAN EFISIENSI TURBIN VORTEX - Tri Rachmanto; Mirmanto; Randi Lelio (Jurusan Teknik Mesin dan Industri, Fakultas Teknik, Universitas Mataram, 2024)
Electrical energy is a very important need for human life in various aspects, both on a large and small scale. One of the efforts to reduce the use of fossil fuels is to use natural resources that are not limited and can be renewed. Micro Hydro Power Plant (MHP) is an alternative source of electricity for the community, one of which is a vortex turbine. The vortex turbine is one type of micro hydro turbine that utilizes a whirlpool as a blade drive. This study examines the effect of blade height variations of 25%, 30%, and 35% of the basin height on power and efficiency. The results showed that the largest turbine power at 25% blade height variation from the basin height with a discharge of 0.009 m3/s was 3.294 Watt with an efficiency of 51.10%. The largest turbine power at an angle variation of 30% of the basin height with a discharge of 0.009 m3/s is 3.364 Watt with an efficiency of 50.66%. The largest turbine power at an angle variation of 35% of the basin height with a discharge of 0.009 m3/s is 4.062 Watt with an efficiency of 62.35%. Turbine power based on two-way anova analysis shows that between variations in turbine height and flow discharge have a significant effect on the turbine power produced and turbine efficiency based on two-way anova analysis shows that between variations in turbine height and flow discharge have a significant effect on the turbine efficiency produced.